2019
DOI: 10.1111/cas.14035
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐143/Musashi‐2/KRAS cascade contributes positively to carcinogenesis in human bladder cancer

Abstract: It has been well established that microRNA (miR)‐143 is downregulated in human bladder cancer (BC). Recent precision medicine has shown that mutations in BC are frequently observed in FGFR3, RAS and PIK3CA genes, all of which correlate with RAS signaling networks. We have previously shown that miR‐143 suppresses cell growth by inhibiting RAS signaling networks in several cancers including BC. In the present study, we showed that synthetic miR‐143 negatively regulated the RNA‐binding protein Musashi‐2 (MSI2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Consistent with our results, miR-143 could target and down-regulate the expression of MSI2 in cervical cancer [18]. Similarly, Tsujino et al indicated that miR-143 could down-regulate MSI2 expression and repress bladder cancer cell proliferation through inhibition of MSI2 expression [22]. Furthermore, Fos-related antigen 2 (FOSL2) was targeted by miR-143-3p in osteosarcoma (OS), thus suppressing OS cell proliferation, migration and invasion [40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our results, miR-143 could target and down-regulate the expression of MSI2 in cervical cancer [18]. Similarly, Tsujino et al indicated that miR-143 could down-regulate MSI2 expression and repress bladder cancer cell proliferation through inhibition of MSI2 expression [22]. Furthermore, Fos-related antigen 2 (FOSL2) was targeted by miR-143-3p in osteosarcoma (OS), thus suppressing OS cell proliferation, migration and invasion [40].…”
Section: Discussionsupporting
confidence: 88%
“…We therefore considered that miR-143-3p was extremely critical, and through the GEO database, significantly low expression of miR-143-3p was identified in TC (Figure 1C). It has been shown that synthetic miR-143 negatively regulated MSI2 in human bladder cancer cell lines [22], and miR-143-3p could be adopted as a potential diagnostic and biomarker of TC. LINC01296 was associated with colorectal cancer [23], ESCC [24] and breast cancer [25], but the regulatory mechanism of LINC01296 in TC is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Noguchi et al demonstrated the combination therapy with the ectopic expression of MIR143 and MIR145 showed the synergistic inhibition of bladder cancer cells through modulating PI3K/AKT and MAPK signaling pathways 11 . Recently, we discovered that MIR143‐3p negatively regulated the KRAS/Musashi‐2 cascade and, consequently, suppressed the cell growth in bladder cancer through downregulation of the KRAS protein expression level at the translational step 55 . Xu et al 56 demonstrated that MIR143 overexpression inhibits KRAS expression and its effector MAPK/ERK signaling pathway, which results in enhanced chemosensitivity to docetaxel in prostate cancer.…”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 99%
“…Musashi has two N‐terminal RNA recognition motifs (RRM), RRM1 and RRM2, that mediate the binding to motifs located at the 3′‐UTR of target mRNA . MSI2 has been reported to act as a potent cooperative oncoprotein in hematopoietic malignancies and a variety of solid tumors …”
Section: Introductionmentioning
confidence: 99%